Social cognitive variables and physical activity during chemotherapy for breast cancer: An intensive longitudinal examination. Issue 3 (6th October 2021) - Auster‐Gussman, Lisa A.; Gavin, Kara L.; Siddique, Juned; Welch, Whitney A.; Solk, Payton; Whitaker, Madelyn; Cullather, Erin; Fanning, Jason; Maria, Cesar Santa; Gradishar, William; Khan, Seema; Kulkarni, Swati; et al.
Abstract: Objective: Although physical activity is associated with better health outcomes in breast cancer survivors (BCS), activity often declines during cancer treatment. Social cognitive theory (SCT) constructs have been associated with physical activity in post‐treatment BCS, but little is known about the relation between these constructs and physical activity during chemotherapy. Methods: BCS ( n  = 67; M age  = 48.6 [SD = 10.3]) undergoing chemotherapy wore accelerometers and completed prompts in the morning and at night assessing same‐day and next‐day exercise self‐efficacy, physical and psychological outcome expectations, and goal‐setting for 10 consecutive days (3 days pre‐, day of, and 6 days post‐chemotherapy dose) at three time points (beginning, middle, and end of chemotherapy). Separate mixed models assessed between‐ and within‐person associations of each of the SCT constructs associations with same‐ and next‐day moderate to vigorous physical activity (MVPA) and light physical activity (LPA), independently. Results: Within‐person differences in all SCT variables were statistically significantly related to same‐day MVPA ( p 's < 0.001) and LPA ( p 's < 0.001). Every one‐point increase in SCT construct related to an increase in MVPA ranging from (a) 3.70 (self‐efficacy) to 8.02 (physical outcome expectations) minute increase in MVPA and (b) 12.72 (self‐efficacy) to 20.38 (physical outcome expectations) increase in LPA that day. No same‐day between‐person effects nor any next‐day effects were significant. Conclusion: MVPA and LPA were related to same‐day within‐person differences in SCT variables. Interventions targeted at increasing or mitigating chemotherapy‐related declines in daily within‐person changes in SCT constructs could help to increase physical activity among BCS during chemotherapy.